IMPLEMENTATION E-GOVERNMENT PUBLIC RELATIONS OF DISASTER COMMUNICATION IN INDONESIA (ANALYSIS OF PACITAN REGENCY, INDONESIA IN THE TSUNAMI DISASTER 2017) - Nurjanah, Adhianty; Ishak, Aswad; Sakir (International Journal of Psychosocial Rehabilitation, 2020)
The geographical condition of Indonesia which is in an active tectonic zone results in Indonesia having high vulnerability to the earthquake and tsunami disasters. Pacitan Regency is one of the disaster-prone areas in East Java Province that has the potential to be affected by the tsunami. Characteristic w territory Pacitan directly adjacent to the beach with the shape of the bay has caused an increasing risk of tsunami. Tsunami disaster is one natural disaster of which has not been discovered yet any tool to predict when exactly it will occur after an earthquake. Early Warning System (EWS), is only a tool to give a signal but does not give predictions when exactly the tsunami disaster came. This study uses a qualitative approach, with the object of research being the Public Relations of the Pacitan Regency Government. This research is a qualitative descriptive study by describing and analysing existing data based on the theory of Government Public Relations and disaster communication. The results showed that the implementation of E-Government of Pacitan Regency carried out by the government with affected communities relating to the provision of financial assistance as well as other basic needs assistance are mainly related to housing assistance to affected communities.